Reliability and validity of the Mental Health Self-management Questionnaire among Chinese patients with mood and anxiety disorders - Wang, Mengmeng; Wang, Jingjun; Wang, Ya; Huang, Xia; Huang, Yalin; Huang, Junqiang; Feng, Yan; Li, Xiaolin (Frontiers in Psychiatry, 2022)
Background Self-management plays an important role in promoting and restoring mental health for individuals with mental health issues. However, there is no valid and reliable Chinese tool assessing the self-management behaviors of people with mood and anxiety disorders. This study aimed to develop a Chinese version of the Mental Health Self-management Questionnaire (MHSQ-C) and to verify its psychometric properties. Methods A total of 440 potential participants were recruited by convenience sampling from June to August 2020. Item analysis and analyses of internal consistency, test-retest reliability, content validity, construct validity and criterion validity were performed. Results Data from 326 participants were used. Three factors obtained via principal component analysis and varimax rotation explained 53.68% of the total variance. The average content validity index was 0.99. The Cronbach’s α coefficient (total: 0.874, clinical: 0.706, empowerment: 0.818, vitality: 0.830) and test-retest reliability (ICC: total: 0.783, 95% confidence interval (CI) [0.616, 0.882], clinical: 0.525, 95% CI [0.240, 0.725], empowerment: 0.786, 95% CI [0.622, 0.884], vitality: 0.748, 95% CI [0.564, 0.862]) were good. The MHSQ-C was well correlated with the Partners in Health scale and showed no floor or ceiling effect. Discussion The MHSQ-C is a reliable and valid tool to evaluate the self-management strategies of patients with mood and anxiety disorders.